Sociological methods in human-geographic researches: features of application - Niemets, Lyudmyla; Lohvynova, Maryna; Suptelo, Olha (Human Geography Journal, 2019)
Human geography, which is an integral branch of contemporary geographical science, relies on a broad methodological basis, using both the general geographical methodological apparatus and the methodological apparatus of related and related sciences. However, taking into account the specifics of the object-subject field of human geography, it is necessary to improve the methodological apparatus, going beyond the use of methods inherent only in geographical science. The anthropogenic factor becomes dominant in all negative changes in the interaction of the “society-human-nature” system. There is a need to replenish the methodological apparatus of human geography through the use of methods of related sciences, in particular, sociology. Sociological methods operate with large amounts of data and can be applied at various stages of socio-geographical research: at the stage of collecting information, its processing and interpretation. Among Ukrainian scientists, human geographers, for now, the use of sociological methods of collecting and processing information is more ignored, unlike foreign scientists. The use of traditional socio-geographical methods and ignoring the methods of related sciences indicate the need for a thorough review of the methodological and methodological foundations of socio-geographical research. This is required by the complexity of the global processes of socio-economic development of modern civilization as a single global socio-geographic system of the planet. At the stage of collecting socio-geographical information, it is important to use sociological methods of collecting information that are indispensable for the study of those features of geographical systems that are not covered by official statistics, as well as for the study of factors of processes and phenomena at the individual and group levels. Sociological research methods have a branched structure, in which they are distinguished as general scientific and special sociological research methods. Sociological methods of data collection can be used in socio-geographical studies, the choice of which depends on the type of goals, objectives, features of the object of study, the material capabilities of the researcher and the capabilities of the toolkit. Sociological methods for collecting information are divided into 5 main classes: survey, analysis of documents, experiment, observation and testing.